Voice of Subalterns in Nepali Dohori Geets - Ramesh Prasad Adhikary (University of Chitral Journal of Linguistics and Literature, 2018)
This research paper is concerned with the question of the representation of subaltern classes–poor, Dalits, women and many other marginalized groups in Nepali Dohori’ Geets. By using the concept of subaltern studies and voice of the voiceless, it is studied about the voice of marginal groups and their representation in Nepali Dohori Geet. So, Dohori Geet, despite being orally transmitted as the part of entertainment program also presents the social situation.